Maqasid Al-Shariah in Micro-entrepreneurs Development: an Overview - Efri Syamsul, Bahri; Mohd Mizan, Mohammad Aslam; Abdullah Alwi, Hj Hasan; Hendro, Wibowo (2019)
The results of this study indicate that maqasid al-shariah which is directly related to the development of micro-entrepreneurs is the principle of protection of descendants (hifdz alnasl) and protection of assets (hifdz al-mal). The protection of descendants (hifdz al-nasl) in the context of developing micro-entrepreneurs is maintaining business continuity and sustainability. Whereas the protection of assets (hifdz al-mal) in the context of developing micro-entrepreneurs is a business that must be managed professionally to grow and make a profit.